Role of kidney function on Nrf2 mRNA levels in type 2 diabetes - Spoto, Belinda; Politi, Cristina; Postorino, Maurizio; Parlongo, Rosa Maria; Testa, Alessandra; Tripepi, Giovanni Luigi; Mallamaci, Francesca; Zoccali, Carmine (BMJ open diabetes research & care, 2024)
IntroductionDiabetic kidney disease (DKD) is a major complication in patients with diabetes and the main contributor to the chronic kidney disease (CKD) global burden. Oxidative stress is a crucial factor in DKD pathogenesis but the role of the antioxidant nuclear factor erythroid 2-related factor 2 (Nrf2) and its molecular regulators has been poorly investigated in man.Research design and methodsIn this case-control study, we analyzed the roles of Nrf2, a transcription factor shielding cells from oxidative stress, its repressor Kelch-like ECH-associated protein 1 (Keap1) and six microRNAs (miRNAs) that potentially suppress Nrf2. We categorized 99 participants into 3 groups: 33 non-dialysis patients with type 2 diabetes with DKD, 33 patients with type 2 diabetes without DKD and 33 control subjects and quantified the gene expression (messenger RNA (mRNA)) levels of Nrf2, Keap1 and 6 miRNAs. Moreover, we studied the correlation between gene expression levels and clinical indicators of kidney health.ResultsIn patients with diabetes with DKD, Nrf2 mRNA levels were significantly lower than in patients without DKD (p=0.01) and controls (p=0.02), whereas no difference in Nrf2 expression levels existed between patients without DKD and controls. Conversely, in patients with and without DKD, Keap1 expression levels were significantly higher than in controls. Of the six miRNAs studied, miRNA 30e-5p showed differential expression, being markedly reduced in patients with DKD (p=0.007). Nrf2 mRNA levels directly correlated with estimated glomerular filtration rate (eGFR) in patients with DKD (r=0.34, p=0.05) and in a formal mediation analysis the eGFR emerged as the first factor in rank for explaining the difference in Nrf2 mRNA levels between patients with and without DKD.ConclusionsThe observed dysregulation in the Nrf2-Keap1 axis and the unique expression pattern of miRNA30e-5p in DKD underscore the need for more focused research in this domain that can help identify novel intervention strategies for DKD in patients with type 2 diabetes.